2012
DOI: 10.1371/journal.pone.0043795
|View full text |Cite
|
Sign up to set email alerts
|

Is “Football for All” Safe for All? Cross-Sectional Study of Disparities as Determinants of 1-Year Injury Prevalence in Youth Football Programs

Abstract: BackgroundFootball (soccer) is endorsed as a health-promoting physical activity worldwide. When football programs are introduced as part of general health promotion programs, equal access and limitation of pre-participation disparities with regard to injury risk are important. The aim of this study was to explore if disparity with regard to parents’ educational level, player body mass index (BMI), and self-reported health are determinants of football injury in community-based football programs, separately or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…After screening titles and abstracts, we retrieved 132 full‐text papers for more detailed study. Finally, 40 papers met the eligibility criteria and were included in the review .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening titles and abstracts, we retrieved 132 full‐text papers for more detailed study. Finally, 40 papers met the eligibility criteria and were included in the review .…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported associations between weight status and acute MSC . Dichotomous data were available from 11 studies and the results were pooled (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In cases where more than 20% of expected frequencies were less than five, Fisher's exact test was used. For the fifth step, three‐way interactions were analyzed using log‐linear analysis . The IBM SPSS Statistics version 24 was used.…”
Section: Methodsmentioning
confidence: 99%
“…For the fifth step, three-way interactions were analyzed using log-linear analysis. 29 The IBM SPSS Statistics version 24 was used. As the aim in this new field of research was to generate new hypotheses for future research, all P values <.05, uncorrected for multiple comparisons, were reported.…”
Section: (6) Interactions Between Pairs Of Different Characteristics mentioning
confidence: 99%
See 1 more Smart Citation